1999
DOI: 10.1021/ci9800965
|View full text |Cite
|
Sign up to set email alerts
|

Response-Surface Analyses for Toxicity to Tetrahymena pyriformis:  Reactive Carbonyl-Containing Aliphatic Chemicals

Abstract: A response-plane has been developed with Tetrahymena pyriformis population growth impairment toxicity data [log 1/50% growth inhibitory concentration (IGC50)], the 1-octanol/water partition coefficient (log Kow), and the energy of the lowest unoccupied molecular orbital (Elumo). A statistically robust plane [log 1/IGC50 = 0.530 (log Kow) -0.890 (Elumo) -0.271, n = 50, s = 0.295, r2 = 0.855, F = 145] was found for reactive carbonyl-containing aliphatic chemicals. These compounds had a variety of electrophilic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Modeling of acute aquatic toxicological endpoints has a long history and is based on the premise that toxicity is governed by the ability of a chemical to reach the active site (e. g. the cellular membrane) and its ability to interact there . In this context transport has usually been quantified by descriptors for hydrophobicity and interaction by descriptors for electrophilicity or more specific interaction such as receptor binding . Many QSAR models for acute aquatic toxicity have been developed on a mechanistic basis, currently more commonly referred to through Adverse Outcome Pathways …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling of acute aquatic toxicological endpoints has a long history and is based on the premise that toxicity is governed by the ability of a chemical to reach the active site (e. g. the cellular membrane) and its ability to interact there . In this context transport has usually been quantified by descriptors for hydrophobicity and interaction by descriptors for electrophilicity or more specific interaction such as receptor binding . Many QSAR models for acute aquatic toxicity have been developed on a mechanistic basis, currently more commonly referred to through Adverse Outcome Pathways …”
Section: Resultsmentioning
confidence: 99%
“…In this context transport has usually been quantified by descriptors for hydrophobicity and interaction by descriptors for electrophilicity or more specific interaction such as receptor binding . Many QSAR models for acute aquatic toxicity have been developed on a mechanistic basis, currently more commonly referred to through Adverse Outcome Pathways …”
Section: Resultsmentioning
confidence: 99%
“…Among them, α , β ‐unsaturated aldehydes such as chemical 5 (acrolein or prop‐2‐en‐1‐al) are systematic outliers in several QSAR studies 43. 44 The toxic potency of acrolein, mediated by a Michael addition toward nucleophiles, is very high and often underestimated. Chemical 4 , crotonaldehyde (but‐2‐en‐1‐al), have the same kind of reactivity than acrolein.…”
Section: Resultsmentioning
confidence: 99%
“…alkanitriles Akers et al, 1999 suggested that haloesters have the potential to exhibit toxicity in excess of base-Ž . line narcosis Schultz and Cronin, 1999 .…”
Section: Methodsmentioning
confidence: 99%